ENRICHMENT OF BREAD AND BAKERY PRODUCTS WITH BIOLOGICALLY ACTIVE SUBSTANCES - Elmurodov Asilbek; Kobilova Nilufar Khudoyshukurovna. (Ustozlar uchun, 2025)
The article explains the possibilities of using new types of additives obtained from local raw materials in the formation of quality indicators of bread and pasta products enriched with biologically active substances and mineral substances.